A new approach to building your personal brand: How to communicate your value to the world - Avery, Jill and Greenwald, Rachel (Harvard Business Review)
For better or worse, in today$1 (Bs world everyone is a brand. Whether you$1 (Bre applying for a job, asking for a promotion, or writing a dating profile, your success will depend on getting others to recognize your value. So you need to get comfortable marketing yourself.- Reproduced s